Biochemical diagnosis of phaeochromocytoma: two instructive case reports. Issue 3 (March 1993) - Stewart, M F; Reed, P; Weinkove, C; Moriarty, K J; Ralston, A J
Abstract : The biochemical features of two patients with phaeochromocytomas illustrate the inadvisability of depending on a single group of analytes for the diagnosis. The first case presented as a surgical emergency with retroperitoneal haemorrhage. Biochemical diagnosis was difficult since total 24 hour urinary free catecholamine excretion was within normal limits in two out of three samples, and only marginally raised in the third with an atypical preponderance of adrenaline. Plasma catecholamine concentrations were also normal. But urinary excretion of the catecholamine metabolites, metadrenaline and 4-hydroxy-3-methoxy mandelic acid (HMMA), was consistently raised. In contrast, the second patient presenting with headache and labile hypertension showed normal metabolite excretion in the face of grossly increased free noradrenaline excretion and raised plasma noradrenaline concentrations. It is therefore recommend that, as well as urinary free catecholamines, one group of their main metabolites, the 3-methoxy amines (normetadrenaline and metadrenaline) or HMMA, should routinely be measured whenever a phaeochromocytoma is suspected.